Stress during Lactation Induces Insulin Resistance Associated with an Increase in Type 1 Cannabinoid Receptors in Liver and Adipose Tissue - Liza Fonseca; Valeska Castillo; Carolina Aguirre; Paulo Silva; Ana M. Ronco; Miguel Llanos (Journal of Nutrition and Metabolism)
Several reports have shown that stress during lactation causes long-term metabolic and hormonal disruptions. In this study, we designed experiments to evaluate the effects of stress during lactation on the abundance of Type 1 cannabinoid/endocannabinoid receptors (CB1R) in epididymal fat and liver and development of insulin resistance in adult mice. During the whole lactation, male mice pups were daily subcutaneously injected (days 1–21) with a saline solution to produce a soft nociceptive stress (NS). Mice body weight and food intake were periodically evaluated. Adult animals were subsequently subjected to an insulin tolerance test and some days later sacrificed to evaluate the amount of epididymal fat and abundance of CB1R and adipophilin in liver and epididymal adipose tissue. Lipoprotein lipase (LPL) activity and circulating levels of leptin, adiponectin, and corticosterone were also evaluated. In this model, NS during lactation significantly increased the amount of epididymal fat and induced insulin resistance in adult mice. In addition, a significantly increased abundance of CB1R and adipophilin in epididymal fat and liver was observed, together with elevated circulating levels of leptin and corticosterone. Adult NS animals also had low plasmatic adiponectin and, although nonsignificant, had a sustained trend to a greater LPL activity associated with epididymal fat. These results indicate that increased abundance of CB1R in liver and epididymal fat alters tissue functionality likely associated with development of systemic metabolic alterations such as insulin resistance in adult mice. All these pathophysiological facts are long-term consequences of nociceptive stress during lactation.